Effects of transcatheter tricuspid valve replacement on hepatic and renal function in severe TR - Zhenzhen Li; Dawei Lin; Jiaxin Miao; Jianing Fan; Fanglin Lu; Xiaochun Zhang; Wenzhi Pan; Daxin Zhou; Junbo Ge (International Journal of Cardiology: Heart & Vasculature)
Objectives: This study evaluated the impact of transcatheter tricuspid valve replacement (TTVR) on renal and hepatic function in patients with severe tricuspid regurgitation (TR). Background: TR is associated with increased morbidity, mortality, and heart failure-related hospitalizations. Venous congestion and reduced forward stroke volume can compromise hepatic and renal function. TTVR has emerged as a promising option for high-risk patients, but its effects remain understudied. Methods: In this prospective, multicenter study, 96 high-surgical-risk patients with severe TR (NYHA functional class III/IV) underwent LuX-Valve TTVR between September 2022 and March 2023. Follow-up at 7, 30, 180, and 360 days assessed cardiac, hepatic (total bilirubin (TBIL), direct bilirubin (DBIL), alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP)), and renal (serum creatinine, urea, uric acid) function. Results: Procedural success was 95.79 %, and 93 patients survived to 12 months. All survivors exhibited TR reduction to less than grade III. Significant hepatic improvement was noted at 12 months, especially among those with preoperative liver dysfunction (LD): total bilirubin decreased from 21.54 ± 11.14 to 18.33 ± 7.82 μmol/L (P = 0.044) and direct bilirubin from 7.95 ± 4.74 to 5.92 ± 2.98 μmol/L (P = 0.005). Renal function remained stable. Conclusions: TTVR is an effective, minimally invasive approach for severe TR, facilitating significant hepatic recovery in patients with preoperative dysfunction while preserving renal function. These findings underscore the reversibility of TR-induced hepatic impairment and demonstrate TTVR’s potential to improve clinical outcomes.